The dual impact of physical exercise on university students’ mental health: the chain mediating effects of mindfulness and psychological resilience - Guo, Jian (Frontiers in Psychology, 2025)
IntroductionMental health issues among university students are increasingly prominent, and effective interventions are urgently needed. Physical exercise has shown potential in improving mental health, but the underlying mechanisms remain unclear. Based on the Conservation of Resources (COR) theory and the Dual - Factor Model of Mental Health, this study aims to explore the dual impact of physical exercise on university students’ mental health and the chain - mediating effects of mindfulness and psychological resilience.MethodsA cross-sectional survey was carried out on 720 students from Chinese universities. Validated instruments were used to measure physical exercise, mindfulness, resilience, and mental health outcomes. SPSS 27.0 and Mplus 8.3 were employed for data analysis, including descriptive statistics, correlation analysis, confirmatory factor analysis, and mediation effect testing.ResultsThe findings show that physical exercise is a proactive resource investment behavior. It significantly enhances students’ mindfulness and resilience. These psychological resources promote positive mental health indicators such as life satisfaction and positive affect, and at the same time, reduce negative factors like psychological distress. The chain mediation analysis indicates that mindfulness and resilience act as interconnected resources, which is in line with the “gain spiral” and “resource caravan” effects in the COR theory.DiscussionThis study provides novel insights by demonstrating how mindfulness and resilience sequentially amplify the psychological benefits of physical exercise. It offers a more detailed understanding of the mechanisms behind the improvement of university students’ mental health. The results have significant theoretical and practical implications, advocating for the integration of exercise, mindfulness, and resilience-building strategies in mental health interventions for university populations.